Modelling and Simulation of Perturb and Observe MPPT Algorithm Based on The PI Controller for Photovoltaic System - Shakoor, Ahlam Mohamad; Taha, Hersh Hasan (Kurdistan Journal of Applied Research, 2022)
The most popular type of renewable energy is photovoltaic (PV) because it is a sustainable source and environmentally friendly. The power generated by a PV system varies with changes in ambient conditions such as temperature and sun radiation; therefore, tracking the maximum power generation from a photovoltaic system independent of temperature and radiation factors is very important. In the literature, a number of techniques for achieving the maximum power point have been presented. In this work, the maximum power point tracking (MPPT) system employing perturb and observe (P&O) algorithm is implemented based on the Proportional and Integral (PI) controller on the proposed PV system to achieve the highest power production from photovoltaic (PV) system and enhance the system performance. The proposed PV system is composed of a Photovoltaic array, DC to DC boost type converter and an MPPT algorithm using perturb and observe method. 1Soltech 1STH-220-P module type was chosen in this study for the simulation and proposed PV The array consists of 40 rows of PV modules connected in parallel, while each row consists of 10 modules connected in a series. All elements of the PV system were simulated using MATLAB/Simulink. The proposed model is used to simulate and optimize the photovoltaic array output current, voltage and power features under various environmental conditions including solar temperature and radiation. The simulation results showed that maximum power point tracking approach using perturbation and observation provide high efficiency to get the highest energy from the PV system regardless of variations in environmental conditions. DC to DC boost converter with perfect performance and high voltage gain is also successfully simulated on the developed PV system.